Medicago truncatula Rop GTPases expression in young nodules - Lucia Kusumawati; Rossana Mirabella; René Geurts (The East Java Biological Society, 2005)
Small GTPases are monomeric guanine nucleotide binding proteins with molecular weight of 21 to 30 kD. Plants have plant-specific small GTPases, termed Rop (Rho GTPases from plants) which serve as signaling proteins in plant signal transduction. To have better understanding on nodulation process in legume, which Rop proteins that play a dominant role in nodule formation would be determined. Therefore, the expression of five Medicago truncatula Rop GTPase genes (MtRops) in young nodules were studied in this experiment. RT-PCR method was used to examine the expression of MtRops. The MtRops expression in inoculated M. truncatula plants were compared with those in uninoculated plants. Results of this studies showed that the expression of MtRop5 and MtRop6 were significantly induced in young nodules, it was suggesting that these Rops may have important role during nodule formation.